HOW DO REMOTE AUDIT AND CLIENT COMPANY SIZE AFFECT AUDIT FEES? - Liza Laila Nurwulan; Helen Maulida (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2023)
This research aims at determining the influence of remote audits and client company size on audit fees at public accounting firms in Pekanbaru. The sample used was Public Accounting Firm (KAP). Based on the results of the research conducted, it can be concluded that there was no relationship between the implementation of the remote audits with the client company size. The implementation of Remote Audits did not have a significant effect on audit fees at the Public Accounting Firm. Then, Client Company Size affected the audit fees at the Public Accounting Firm. While, Remote Audits and Client Company Size simultaneously affected audit fees at the Public Accounting Firm in Pekanbaru.